What Sustains Fiscal Consolidations in Emerging Market Countries? - Clements, Benedict (IMF Working Papers; Working Paper ;, 2003)
This paper examines the factors affecting the persistence of fiscal consolidation in 25 emerging market countries during 1980-2001. It proposes a new approach for defining spells of fiscal consolidation. The results indicate that the probability of ending a fiscal adjustment is affected by the legacy of previous fiscal failures, the size of the deficit, the composition of spending, and level of total revenues. There is also some evidence that the initial debt stock, exchange rate developments, inflation, and the unemployment rate have an impact on the persistence of adjustments.